2022
DOI: 10.3390/jpm12060935
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease CSF Biomarker Profiles in Idiopathic Normal Pressure Hydrocephalus

Abstract: Patients with idiopathic normal pressure hydrocephalus (iNPH) frequently show pathologic CSF Aβ42 levels, comparable with Alzheimer’s Disease (AD). Nevertheless, the clinical meaning of these findings has not been fully explained. We aimed to assess the role of AD CSF biomarkers (Aβ42, Aβ42/Aβ40, p-tau, t-tau) in iNPH. To this purpose, we enrolled 44 patients diagnosed with iNPH and 101 with AD. All the patients underwent CSF sampling. We compared CSF biomarker levels in iNPH and AD: Aβ42 levels were not diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The iNPH disease is a neurodegenerative disease and subtype of dementia with close histopathological overlap towards AD 58 ; for example, accumulation in the brain of Aβ and/or tau is seen in a significant proportion of iNPH subjects 59 . Moreover, previous studies showed a comparable reduction of CSF production and turnover in AD and iNPH patients 60 , though CSF Aβ40, Aβ42, and T-/P-tau also were able to differentiate iNPH from AD subjects 61 . iNPH involves impaired glymphatic function 12 , 62 , which was proposed as a common mechanism behind dementias and AD 63 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The iNPH disease is a neurodegenerative disease and subtype of dementia with close histopathological overlap towards AD 58 ; for example, accumulation in the brain of Aβ and/or tau is seen in a significant proportion of iNPH subjects 59 . Moreover, previous studies showed a comparable reduction of CSF production and turnover in AD and iNPH patients 60 , though CSF Aβ40, Aβ42, and T-/P-tau also were able to differentiate iNPH from AD subjects 61 . iNPH involves impaired glymphatic function 12 , 62 , which was proposed as a common mechanism behind dementias and AD 63 .…”
Section: Discussionmentioning
confidence: 73%
“…In line with this observation, iNPH patients not responding to shunt surgery had increased CSF T-tau concentration 64 , 65 , and also increased CSF NfL concentration 65 . Cognitively impaired iNPH patients also had higher P-tau concentration than cognitively intact iNPH subjects 61 . They also presented a lower Aβ42/Aβ40 ratio 61 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In an attempt to use CSF biomarkers to differentiate iNPH from subcortical ischemic vascular disease (SSVD), Manniche et al (2020) suggested that lower concentrations of Aβ42 and t-tau were found in patients with iNPH compared to patients with subcortical vascular dementia, while concentration of p-tau in the CSF was similar in both diseases [ 47 ]. Said et al (2022) suggested that in iNPH patients CSF concentration of Aβ42 was higher and those of t-tau and p-tau were lower than in AD patients [ 48 ], while Mazzeo et al (2022) found that Aβ42/Aβ40, p-tau, and t-tau were significantly lower in iNPH than in AD and that Aβ42 concentration was similar in these two diseases [ 49 ]. Finally, all amyloid fragments’ CSF concentrations were found to be decreased in iNPH and SSVD compared to healthy individuals, with iNPH patients having lower concentrations than those with SSVD [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mainly focused on the potential of classical AD cerebrospinal fluid (CSF) biomarkers in differential diagnosis of iNPH from similar clinical entities and long-term response after shunt surgery 11,12 . Lower levels of neurofilament light (NfL), amyloidβ 1-42 (Aβ 1-42 ), amyloidβ 1-40 (Aβ 1-40 ), total tau (t-tau), and phosphorylated tau 181 (p-Tau181) have been associated with long-term improvement in gait outcomes after shunt surgery [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%